Study of some factors affecting maternal weight gain during pregnancy - Ranaweera, C.P (My University, 2005)
Average maternal weight gain in the study was 8.69kg with the standard deviation of 3.02kg weight gain ranging from3kg to 18kg of the study sample. 30.2 percent gained less than 7kg while 34.3 percent gained more than 9kg and 34.3 percent mothers gained between 7kg and 9kg. In the unvaried analysis, factors like BMI, and nutrition showed a positive and significant relationship with maternal weight gain. (p0.05) Monthly income shows a highly significant gain. (p0.01). This study sample showed negative relationship of maternal weight gain with age and ethnicity. Home visits by Public Health Midwives (PHM) are highly positive influencing factors for awareness raising. The major source of information on weight gain during pregnancy was the PHM and the majority of services were received from local ANC clinics. The incidence of Low Birth Weight (LBW) decreased with mother's ages. It was highest in the . 19 years age group and declined, thereafter, incidence of LBW increase with age, suggesting that elderly women were more prone to produce LBW babies, although one would expect a significant rise in the incidence of LBW among grand multies. The study result showed marginal criteria. It is recommended that greater emphasis should be given to health education in the field and local clinics by using correct IEC. Home visits by PHM should be promoted to reach every household. The health volunteers could be used for this purpose. Counseling, increased access to knowledge regarding proper nutrition, adequate rest during pregnancy, importance of family planning and developing a system to recommend maternal weight gain based on BMI were proposed as measures to reduce the incidence of low birth weight babies and to uplift health of mothers after delivery